The Nature of Collaboration in Collaborative Editing Task: Evidence of First Language Use and Patterns of Interaction - Haloho, Agnes Vebian; Lasito, Lasito (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2023)
This study aims to investigate the nature of collaboration in an EFL collaborative editing task, particularly the evidence of first language (L1) use and patterns of interaction that students used and formed when working with a passage editing task. The study recruited 22 students in grade eleven of SMA Xaverius, Pringsewu. The study follows the framework of Storchs’ dyadic interaction pattern (2002) and Storch and Aldosari's L1 function to code and analyze its data. The data of this study were transcripts of 11 pairs of students participating in an EFL editing task. This study found that the number of first-language use is bigger than the target language use. In percentage, the student average produced around 55,7% of words in the first language and 43,3% of words in the second language. The main function of the L1 is for grammar deliberation, followed by the deliberations over vocabulary (20,2% of all L1 turns), task management (11,1% of all L1 turns), mechanics deliberation (5% of all L1 turns), and last is generating ideas (4,5% of all L1 turns). The main interaction pattern used by the learners was the collaborative pattern (eight out of eleven pairs). The remaining pairs fit dominant/dominant, dominant/passive, and Expert/novice for each of the pair, respectively.